2005
DOI: 10.1074/jbc.m508460200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-Protein Is Degraded by Cellular Angiotensin-converting Enzyme (ACE) and Elevated by an ACE Inhibitor

Abstract: Human genetic data have associated angiotensin-converting enzyme (ACE) with Alzheimer disease (AD), and purified ACE has been reported to cleave synthetic amyloid ␤-protein (A␤) in vitro. Whether deficiency in ACE activity, arising from genetic alteration or pharmacological inhibition, can decrease A␤ degradation and allow A␤ accumulation in intact cells is unknown. We cloned ACE from human neuroblastoma cells and showed that it had posttranslational processing and enzymatic activity typical of the endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
2
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(243 citation statements)
references
References 49 publications
10
220
2
11
Order By: Relevance
“…A recent in vivo study also shows that ACE inhibitors at doses similar to those used clinically do not increase the levels of brain A␤s (Eckman et al, 2006). Previous studies using purified human seminal plasma ACE and cultured cells showed that ACE degrades A␤s and ACE inhibition increases A␤ levels in APP-and ACE-transfected cells (Hu et al, 2001;Hemming and Selkoe, 2005;Oba et al, 2005). However, these findings seem to disagree with those of in vivo studies.…”
Section: Discussioncontrasting
confidence: 49%
“…A recent in vivo study also shows that ACE inhibitors at doses similar to those used clinically do not increase the levels of brain A␤s (Eckman et al, 2006). Previous studies using purified human seminal plasma ACE and cultured cells showed that ACE degrades A␤s and ACE inhibition increases A␤ levels in APP-and ACE-transfected cells (Hu et al, 2001;Hemming and Selkoe, 2005;Oba et al, 2005). However, these findings seem to disagree with those of in vivo studies.…”
Section: Discussioncontrasting
confidence: 49%
“…However, recent large genome-wide association studies did not identify ACE as a significant genetic risk factor (68 -70). However, recombinant ACE is capable of cleaving both A␤40 and A␤42 in vitro and thereby decreases A␤ aggregation and toxicity (71)(72)(73). We also observed efficient cleav- age of A␤ by ACE.…”
Section: Maldi-tof-ms Analysis Of Cleavage Products Of Npa␤ and Pa␤supporting
confidence: 48%
“…Accumulated Aβ can be removed by Aβ-degrading enzymes, such as neprilysin (NEP) [14], insulin-degrading enzyme (IDE) [15], endothelin-converting enzyme [16] and angiotensinconverting enzyme [17]. All these protease activities respond elaborately to diverse genetic and biochemical mediations.…”
Section: Introductionmentioning
confidence: 99%